2012
DOI: 10.1515/znc-2012-5-606
|View full text |Cite
|
Sign up to set email alerts
|

Major Constituents and Cytotoxic Effects of Ajuga chamaecistus ssp. tomentella

Abstract: The n-butanolic fraction of a methanolic extract (80%) from aerial parts of Ajuga chamaecistus ssp. tomentella was analysed using different chromatographic methods. Column (CC) and high-performance liquid chromatography (HPLC) were used for isolation and purifi cation. 13C, 1H NMR, H-H COSY, HSQC, HMBC, and ESI-MS were employed for identifi cation of the compounds isolated from this fraction. The structures of the compounds were determined to be cis-melilotoside (1), trans-melilotoside (2), lavandulifolioside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The genus Ajuga has been reported to contain iridoids, phenylethanoid glycosides, flavonoids, anthocyanins and o-coumaric acid derivatives (De la Torre et al 1997;Takasaki et al 1998;Akbay et al 2002Akbay et al , 2003Sadati et al 2012;Inomata et al 2013). Among the isolated compounds in this study, harpagide or its acetyl derivative 8-O-acetylharpagide were also reported from other genera of Lamiaceae including Stachys (Calis et al 1992), Lamium (Alipieva et al 2003) and Galeopsis (Venditti et al 2013).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The genus Ajuga has been reported to contain iridoids, phenylethanoid glycosides, flavonoids, anthocyanins and o-coumaric acid derivatives (De la Torre et al 1997;Takasaki et al 1998;Akbay et al 2002Akbay et al , 2003Sadati et al 2012;Inomata et al 2013). Among the isolated compounds in this study, harpagide or its acetyl derivative 8-O-acetylharpagide were also reported from other genera of Lamiaceae including Stachys (Calis et al 1992), Lamium (Alipieva et al 2003) and Galeopsis (Venditti et al 2013).…”
Section: Discussionsupporting
confidence: 56%
“…Among the isolates, cis-and transmellitoside (3 and 4) have previously been reported from only one Ajuga species, namely Ajuga chamaecistus ssp. tomentella (Sadati et al 2012). This is the second report of the presence of mellitoside from a member of the Ajuga genus.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The glucose moiety, which can be assigned a β-configuration on the basis of the coupling constant of the anomeric proton at δ 5.05 (d, J = 7.2 Hz, 1H, H-1′) [33] is attached to the C-2 (δ 153.81) position. Based on the analysis of the spectroscopic data and literature data, it can be concluded that compound 1 is cis-coumaric acid-2-O-β-D-glucopyranoside (cis-melilotoside, Figure 2) [30,31]. This is the first report on the isolation of cis-melilotoside (1) from M. officinalis.…”
Section: Characterization Of Compounds Isolated From Meoh Extract Of M Officinalis Seedsmentioning
confidence: 87%
“…cis-Melilotoside has previously been reported from several other plants such as Ajuga chamaecistus ssp. Tomentella and Mikania laevigata [30,34]. Compound 2 was isolated from the MeOH extract of the seeds of M. officinalis as a white powder and has a melting point of 70-71 o C. The UV-Vis spectrum of 2 in MeOH revealed an absorption maximum (λ max ) at 274 and the IR spectrum in KBr showed absorption bands at 1729, 1288, 1124 cm -1 due to the presence of an aromatic ring and an α,β-unsaturated carbonyl carbon.…”
Section: Characterization Of Compounds Isolated From Meoh Extract Of M Officinalis Seedsmentioning
confidence: 99%